(untitled) (Movimento-revista de educação, 2017)
Este trabalho tem como escopo discutir o conceito de intelectual orgânico conforme o pensamento de Antonio Gramsci, destacando a sua tarefa como organizador da vontade coletiva dos subalternos a fim de superar a sociabilidade capitalista e implantar um novo ordenamento social fundado na perspectiva socialista. Nesse sentido, o intelectual orgânico vinculado aos subalternos emerge como educador que, dialeticamente, educa e se educa como pessimista e otimista para contribuir com o processo de elevação dos sujeitos governados à condição de governantes de uma nova ordem social. Palavras-chave: Intelectual orgânico; Vontade coletiva; Subalternos. The organic intellectual as trainer of the collective will of the subalterns: notes from Antonio Gramsci Abstract This work aims to discuss the concept of organic intellectual according to the thought of Antonio Gramsci, highlighting his task as organizer of the collective will of subordinates in order to overcome capitalist sociability and implant a new social order based on the socialist perspective. In this sense, the organic intellectual linked to subalterns emerges as an educator who dialectically educates and educates himself as a pessimist and optimist to contribute to the process of elevating the governed subjects to the condition of being governors of a new social order. Keywords: Organic Intellectual; Collective will; Subalterns.